2021
DOI: 10.1001/jamanetworkopen.2021.9375
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Medical Cannabis Use and Associated Health Conditions Documented in Electronic Health Records Among Primary Care Patients in Washington State

Abstract: Key Points Question Among primary care patients, what is the prevalence of electronic health record documentation of medical cannabis use and health conditions for which cannabis use might have benefits and risks? Findings In this cross-sectional study of 185 565 patients, 2% had past-year medical cannabis use documented in their electronic health records. Among patients with documented medical cannabis use, 44.5% had documented health conditions for which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 54 publications
4
31
1
Order By: Relevance
“…Conversely, it is possible that some of this association is due to people with medical conditions using cannabis to manage or alleviate their symptoms [ 13 , 37 39 ]. These findings indicate a stronger association between cannabis use and medical diagnoses than that found by Matson et al [ 17 ] in their study of EHR data from Washington State. These differences may be attributable to the fact that unlike Washington State, California was a medical marijuana state at the time of this study, but had not yet legalized cannabis use generally.…”
Section: Discussioncontrasting
confidence: 44%
See 4 more Smart Citations
“…Conversely, it is possible that some of this association is due to people with medical conditions using cannabis to manage or alleviate their symptoms [ 13 , 37 39 ]. These findings indicate a stronger association between cannabis use and medical diagnoses than that found by Matson et al [ 17 ] in their study of EHR data from Washington State. These differences may be attributable to the fact that unlike Washington State, California was a medical marijuana state at the time of this study, but had not yet legalized cannabis use generally.…”
Section: Discussioncontrasting
confidence: 44%
“…Under one percent of the sample in this study had documentation of CU or CUD in their EHR, compared to studies of EHR data from Washington State, which found EHR-documented cannabis use rates between 15 and 22% [ 16 , 17 ]. Some of this difference may be due to higher levels of adult CU, frequent cannabis use, and CUD in states like Washington that allow non-medical marijuana use [ 23 ].…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations